Extracting phreatic evaporation from remotely sensed maps of evapotranspiration - Brunner, Philip; Li, H. T.; Kinzelbach, Wolfgang; Li, W. P.; Dong, X. G. (My University, 2008)
One of the most important parameters related to soil salinization is the direct evaporation from the groundwater (phreatic evaporation). If the groundwater table is sufficiently close to the surface, groundwater will evaporate through capillary rise. In recent years, several methods have been suggested to map evapotranspiration (ET) on the basis of remote sensing images. These maps represent the sum of both transpiration of vegetation and evaporation from the bare soil. However, identifying the amount of phreatic evaporation is important as it is the dominant flux in the salt balance of the soil. The interpretation of stable isotope profiles at nonirrigated areas in the unsaturated zone allows one to quantify phreatic evaporation independently of the transpiration of the vegetation. Such measurements were carried out at different locations with a different depth to groundwater. The benefit is twofold. (1) A relation between phreatic evaporation rates and the depth to groundwater can be established. (2) By subtracting the measured values of phreatic evaporation from remotely sensed values of ET, vadose ET consisting of transpiration and excess irrigation water in the unsaturated zone can be estimated at the sampling locations. A correlation between the normalized differential vegetation index and the calculated vadose ET rates could be established (R(2) = 0.89). With this correlation the contribution of phreatic evaporation can be estimated. This approach has been tested for the Yanqi basin located in western China. Finally, the distribution of phreatic evaporation was compared to a soil salinity map of the project area on a qualitative basis.
Keywords: surface-energy balance; sensing algorithm; fluxes; basin; water; temperature; validation; vegetation; lake